Corrosion Inhibition of Galvanic Couple Copper Alloy/Mild Steel in Cooling Water System - S. Yaro, Aprael; A. Idan, Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The driving idea for the present work was to combine the effect of polyvinyl alcohol (PVA) as corrosion inhibitor with the distance between the anodic and cathodic elements of the galvanic cell, beside their area ratio, in scope of synergistic suppression of galvanic corrosion on Cu/Fe model couple, using weight loss method. The performance affecting galvanic corrosion process has been tested for three major factors affect the process: 1. Four PVA inhibitor concentrations were selected to be (0, 1000, 4000 and 7000 ppm) in simulated cooling water. 2. Two cathode: anode area ratios as 1:1 and 2.4:1. 3. Two distances apart cathode – anode as 3 and 7 cm. Maximum corrosion inhibition achieved was 86% which indicates that increasing inhibitor concentration leads to decrease dissolution process followed hydrogen evaluation Cu electrode as cathode element in galvanic cell.